A service-oriented approach for developing adaptive distribution chain. (27th December 2006) - Davidrajuh, Reggie
This paper presents a service-oriented approach for the development of adaptive distribution chain. The distribution chain presented in this paper achieves all the three objectives of an adaptive chain: first, to achieve variability, this paper proposes an approach that uses iterations to fine tune the modules that make up the distribution chain; second, to achieve visibility, it proposes web services based Service Component Architecture (SCA) for the implementation of the distribution chain. Finally, mathematical modelling and simulation of the distribution chain is proposed for assuring the velocity.